Fostering an Understanding of Students' Rights and Obligations to Form an Attitude of Responsibility in Elementary School - Afifah Dwi Ramadhani; Abdullah Taufik Ritonga; Herdila Herdila; Nurhafizah Lubis; Zulhidah Zulhidah (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This study aims to describe how the understanding of rights and obligations can be used as a basis for instilling an attitude of responsibility in elementary school students. An understanding of rights, such as the right to learn and feel safe, as well as obligations, such as obeying the rules and respecting teachers, are key to the formation of students' character from an early age. This research uses a literature study method by collecting data from various sources such as books, scientific journals, articles, and relevant thesis. The data were analyzed descriptively to illustrate how the concept of rights and obligations is integrated in the educational process, especially through learning Pancasila Education and habituation in the school environment. The results showed that the instillation of responsibility attitudes in students was greatly influenced by the extent to which they understood the reciprocal relationship between rights and obligations. Teachers have a central role as a mentor, role model, and facilitator in helping students carry out their obligations consistently. Habituation through routine tasks such as class picketing, tidiness of study, and adherence to rules has been proven to be effective in increasing students' awareness of responsibility. In addition to the school factor, parental support and a conducive environment are also an important part in strengthening character formation. However, several factors such as low self-awareness, excessive use of mobile phones, and lack of parental attention are still obstacles that need to be overcome through collaboration between schools and families. Overall, the understanding of rights and obligations is an important foundation in forming a sustainable attitude of responsibility among elementary school students.